Optimasi Tata Kelola Sistem Informasi Industri Tape Melalui Pengembangan Way Finding Industri Tape Desa Banjarsari - Alby Aruna; Mohamad Firzon Ainur Roziqin; Eka Putri Surya; Abdul Rahman Prasetyo; Adinda Marcelliantika; Ginanjar Atma Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The optimization of information system management in the tape industry through the development of Way Finding in Banjarsari Village aims to enhance operational efficiency and visitor experience. This program integrates wayfinding technology with the information system to provide accurate and interactive navigation guidance in the tape industry area. The methods used include the development of a digital wayfinding application, technical training for industry managers, and evaluation of system effectiveness through user feedback. The results indicate increased visitor satisfaction and more efficient management. The implementation of this optimized information system is expected to support the development of a more modern and attractive tape industry in Banjarsari Village.